IMPLEMENTASI VIRTUAL LEARNING POLTEKKES KEMENKES KUPANG - Waaangsir, Ferry WF; Saleh, Ummi Kaltsum S; Kusmiyati, Kusmiyati; Nugraha, Yohanes C (Universitas Tanjungpura, 2022)
The COVID-19 pandemic requires the learning system to be carried out online. One of the online learning methods developed by